2016
DOI: 10.1007/s11356-016-7428-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pyrolysis temperature on lead immobilization by chemically modified coconut fiber-derived biochars in aqueous environments

Abstract: Biochar has received widespread attention as an eco-friendly and efficient material for immobilization of toxic heavy metals in aqueous environments. In the present study, three types of coconut fiber-derived biochars were obtained by pyrolyzing at three temperatures, i.e., 300, 500, and 700 °C. In addition, nine types of biochars were prepared by chemical modification with ammonia, hydrogen peroxide, and nitric acid, respectively, which were used to investigate changes in physico-chemical properties by inter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Parallel to the result they obtained using the coconut fiber adsorbent, they found out the activation with KOH does not improve the adsorbent's ability to remove elemental mercury as the adsorption capacity of char adsorbent was higher (Q ¼ 3142.57 μg/g) than that of the activated char (Q ¼ 57.77 μg/g). The finding of this study can be supported by the finding of Wu et al's where char that were produced at high pyrolysis temperature may be resistant to chemical modification [110].…”
Section: Coconut Pithsupporting
confidence: 84%
See 1 more Smart Citation
“…Parallel to the result they obtained using the coconut fiber adsorbent, they found out the activation with KOH does not improve the adsorbent's ability to remove elemental mercury as the adsorption capacity of char adsorbent was higher (Q ¼ 3142.57 μg/g) than that of the activated char (Q ¼ 57.77 μg/g). The finding of this study can be supported by the finding of Wu et al's where char that were produced at high pyrolysis temperature may be resistant to chemical modification [110].…”
Section: Coconut Pithsupporting
confidence: 84%
“…On the other hand, Wu et al conducted an extensive research on coconut fiber utilization for removal of Pb(II) ions from aqueous solution [110]. In their study, the coconut fiber was carbonized at 300, 500, and 700 C and was treated with different chemicals such as H 2 O 2 , NH 4 .OH, and HNO 3 as to study its effect on Pb(II) removal.…”
Section: Coconut Fibermentioning
confidence: 99%
“…Pyrolysis of tire waste has been carried out using different reactors, including fixed bed reactors (de Marco et al, 2001), thermogravimetric analysis (Teng et al, 1998), spouted beds (Lopez et al, 2009), fluidized bed pyrolysis (Kaminsky and Mennerich, 2001), vacuum pyrolysis (Roy et al, 1995), and rotary kiln (Li et al, 2004). The primary objective of these studies was to investigate the effect of various process variables such as temperature, reaction time, feedstock size and type, and scale of the reactor on pyrolysis products and how to increase the quantity of produced liquid oil, but not the quality of liquid oil (Kraiem et al, 2016;Wu et al, 2016;Wan et al, 2014). For example, Cunliffe et al (1998) concluded that increase in temperature from 450 to 600 °C decreased the liquid oil yield from tire waste pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar with high porosity can be applied as adsorbent of heavy metals from soil, because the active sites on biochar can attract and reduce the toxic elements (Wu et al 2016;Karimi et al 2020).…”
Section: Recalcitrance and Stabilitymentioning
confidence: 99%